Small Hive Beetle, Aethina tumida Murray (Insecta: Coleoptera: Nitidulidae) - James D. Ellis; Amanda Ellis (EDIS)
EENY-474, a 5-page illustrated fact sheet by James D. Ellis and Amanda Ellis, is part of the Featured Creatures collection. It describes this small beetle native to sub-Saharan Africa, which can cause considerable damage to colonies of European honey bees outside of its host range — distribution, description, life cycle, economic importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, June 2010.